Real-Time Big Data Analytics: Applications and Challenges - Uthra, R; Mahalakshmi, A (International Journal of Computer Sciences and Engineering, 2025)
In recent years, time-significant processing or real-time processing andanalytics of big data have received a huge amount of attentions. There are many areas/domains where real-time processing of data and making timely decision can saves thousands of human lives, minimizing the risks of human lives and resources, enhance the quality of human lives, enhance the chance of effectiveness, capableresources management etc. This paper has describedreal-time big data analytics applications and the tools used and the technical challenges faced by the applications. In addition it presents a general overview of big data to describe a background knowledge on this extent. Some examples of these domains includesecurity, healthcare, transportation, military, and natural disaster. Several big data applications in these domains rely on fast and timely analytics based on available data to make excellence decisions